ANALISIS PENGGUNAAN TROTOAR DI KAWASAN KOTA CIANJUR - Sekaryadi, Yudi; Mohamad, Dadang; Ramadhan Iskandar, Muhammad (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2024)
Sidewalks are provided for pedestrians located in road use areas, given a surface layer with a higher elevation than the surface of the road pavement, and generally parallel to the vehicle traffic lane. The aim of this research is to analyze the Level of Service (LoS) of sidewalks and the appropriate functions of sidewalks. and assess pedestrian path facilities in accordance with established requirements and standards. The research location is in the urban area of Cianjur City, namely the sidewalks of Jalan Adi Subuat, Jalan Siti Jenab, Jalan Suroso, Jalan Taifur Yusuf, and Jalan Ir H Juanda. The method used is the analytical survey method, namely the method of conducting a survey at the location studied. The results of the analysis show that the level of service (LoS) of the Jalan Adi Sucipta sidewalk is category D, the level of service (LoS) of the sidewalk of Jalan Siti Jenab is category D, the level of service (LoS) of the sidewalk of Jalan Suroso is category D , Level of Service (LoS) of Jalan Taifur Yusuf Category D, and Level of Service (LoS) of Jalan Ir H Juanda category C. Categories C and D are categories that are still comfortable to use but there are a few differences in categories C and D and the facilities meet applicable standards. Conclusion: Level of Service (LoS) in Cianjur City is in the comfortable category to use.